من رمي بالوقف في القرآن من المحدثين وأثر ذلك على مروياتهم: دراسة نظرية - عبدالفتاح، ناصر أبو عامر عبدالسلام (جامعة الأزهر - کلية أصول الدين والدعوة الإسلامية بالمنوفية, 2020)
يهدف هذا البحث إلى رفع الإشكال الوارد عن هؤلاء الرواة الذين رموا بالوقف في القرآن، والبالغ عددهم سبعة عشر راويا، والذين لهم رواية في الكتب الستة، وغيرها، وبيان أثر ذلك على مروياتهم، من خلال جمع تراجمهم ودراستها، ثم التوصل إلى نتيجة واضحة في الحكم على هؤلاء الرواة، وقد انتهى البحث إلى عدة نتائج أهمها: أن البدعة: "كل أمر محدث في الدين، خالف الأصول، أو ناقض ما واظب عليه الرسول (صل الله عليه وسلم) أو هدم مقاصد الشريعة"، وقد اختلفت العلماء في تقسيم البدعة، وأن ما ثبتت بدعته ثبتت حرمته، وما وصف بكونه بدعة ممدوحة، فليس بدعة من كل وجه على الحقيقة، بل هو بدعة من حيث اللغة، والواقف في القرآن من يقول: القرآن كلام الله ولا يزيد على ذلك، وتسمى بدعة الوقف في القرآن، وقد ظهرت في الدولة العباسية زمن المأمون، والواقفة على أقسام ثلاثة: الشكاك، والساكتون والجاهلون، وحكم هؤلاء إما أنهم مبتدعة، أو مرتدون، أو كفار، ثم إن توبة المرتد تكون بدخوله من الباب الذي خرج منه، فتوبة الواقفة بأن يعترفوا ظاهراً بأن القرآن كلام الله تعالى على الحقيقة، محكم غير مخلوق، و الرمي بالوقف في القرآن بدعة من البدع التي طعن المحدثون بها الرواة بسبب الاعتقاد، مثلها مثل الإرجاء، والتشيع، والرفض…، وغير ذلك من البدع التي ابتلي بها جماعة من الرواة، وليس ذلك بمانع من قبول روايتهم، كما قرره الذهبي وابن حجر، لأن كل طائفة تدعي أن مخالفيها مبتدعة، وقد تبالغ فتكفر مخالفها، والمعتمد أن الذي تُرد روايته من أنكر أمرا متواترا من الشرع معلوما من الدين بالضرورة، وهذا هو الحق الجدير بالاعتبار، والعبرة في الرواية بصدق الراوي وأمانته، وإتقان الحفظ، ثم يوصي البحث طلبة العلم بلزوم الشيوخ والأخذ عنهم مباشرة، مع قراءة المقدمات النفيسة لكتب السنة وشروحها، كمقدمة فتح الباري، وغيرهما من مقدمات الشروح المعتبرة، واستخراج ما فيها من الفوائد والنكت العلمية التي ينتفع بها المشتغلون بالسنة وعلومها.
This study aims to shed some light upon a major event happened during the ABBASSY PERIOD regarding the notion of Createdness of the Holly Quran ordeale): Createdness refers to the Islamic doctrinal position that the Qur’an was created, rather than having always existed and thus being "uncreated". In the Muslim world the opposite point of view that the Quran is uncreated is the accepted stance among the majority Sunni Muslims and the Kharijites while minority sects Shia Twelvers and Zaydi believe the Quran is created. The dispute over which was true became a significant point of contention in early Islam. The Islamic rationalist philosophical school known as the Mu'tazila held that if the Quran is God's word, logically God "must have preceded his own speech" .The Qur'an, of course, expresses God's eternal will, but the work itself must have been created by Him at some point in time. Traditionists, on the other hand, held that numerous records of the words, actions, or approval of Muhammad (aḥādīth) support the contention that as God's speech, the Qur’an is an attribute of God and therefore "uncreated". That the question of the createdness of the Qur’an is, among other things, a hermeneutical issue is reflected in the variety of arguments and issues that associate with it whether the Qur’an or the traditions assert the Qur’an’s createdness, what “created” means, and whether and how this affects the standing of these texts as authoritative and as a consequence, the status of those who study them. Where the Qur’an is understood as the word of God, and the words and example of the Prophet transmitted through hadith also attain to divine significance, if the Qur’an cannot be taken to assert its own createdness, for the doctrine of createdness to be true the traditions would have to support it. Indeed, to admit the insufficiency of the hadith corpus to adjudicate what with the institution of the mihna becomes such a visible dispute would necessarily marginalize the authority of traditions. Thus it is not by accident that al-Ma’mun decides to administer the test on religious scholars. The caliph al-Ma’mun issued the proclamation of the doctrine of the createdness of the Qur'an. The proclamation was followed by the institution of the Mihna six years later, approximately four months before his sudden death .The Mihna continued under his successors, al-Mu’tasim and al-Wathiq, before al-Mutawakkil abolished it .This particular doctrine was well known to be embraced by the Mu'tazilite school during this period. Muʿtazilites believed that good and evil were not always determined by revealed scripture or interpretation of scripture, but they were rational categories that could be established through unaided reason. Traditional scholarship viewed the proclamation of doctrine and the Mihna where al-Ma’mun tested the beliefs of his subordinates as linked events, whereby the caliph exercised his religious authority in defining orthodoxy, and enforced his views upon others through his coercive powers as ruler. Al-Ma’mun's motivations for imposing his beliefs upon the members of his government (such as his judges, for the scope of the Mihna was not extended to examining the beliefs of the commoners in the manner of the European Inquisitions) were attributed to his Mu'tazilite intellectual tendencies, his sympathies towards Shi’ism, or a shrewd decision to consolidate his religious authority during a time where the 'ulama were starting to be seen as the true guardians of religious knowledge and the Prophet's traditions.
Keywords: علوم الحديث -- علم الجرح والتعديل -- علم الرجال -- الوقف في القرآن -- البدعة